Becoming Ray Bradbury - Eller, Jonathan R., 1952- (University of Illinois Press, 2013)
'Becoming Ray Bradbury' chronicles the making of an iconic American writer. Jonathan R. Eller measures the impact of the authors, artists, illustrators and filmmakers who stimulated Ray Bradbury's imagination throughout his first three decades.